An isokinetic profile of trunk rotation strength in elite tennis players - Ellenbecker, T. S.; Roetert, E. P. (Medicine and Science in Tennis, 2004)
The changes in stroke production in the modern game of tennis have increased the demands on trunk rotation in elite tennis players. Unlike the shoulder where unilateral strength adaptations have been identified, no study to date has objectively quantified side to side rotational trunk strength in elite tennis players.